El-Zaki Transform Method for Solving Applications of Some Integral Differential Equations (Contemporary Mathematics, 2025)
Integral equations have close contact with many different science and engineering problems, such as contact problems in the theory of elasticity, potential theory, fluid mechanics, quantum mechanics, healthcare, and others. So, in this presentation, we will study the following models: determining the blood glucose concentration by using Volterra integral equations. Integral equations are used in electrical engineering applications. Abel's integral equation has applications in a variety of scientific domains, including plasma diagnostics, radio astronomy, and optical fibre evaluation. This is an ancient example of an integral equation. The El-Zaki transformation method is used to solve three models and compare the exact and approximate results. The findings are calculated using Maple 18.
Keywords: volterra integral equation; El-Zaki transformation method; blood glucose concentration electrical engineering; Abel's integral equation